2017
DOI: 10.4172/2375-4273.1000188
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Progress of Policies on Cervical Cancer in South Africa

Abstract: Cervical cancer is the second most common cancer in South African women but the most frequently encountered cancer in black women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Persons with CIN2+ were referred for colposcopic evaluation with biopsy, and women with confirmed lesions or cancer were treated with large loop excision of the transformation zone (LLETZ) or hysterectomy, respectively [ 18 ]. High loss-to-follow-up resulted in low levels of effective treatment with this three-visit strategy [ 19 ]. Effective treatment was lower for women living with HIV, reflecting lower sensitivity and specificity with cytology [ 9 , 10 ] and higher treatment failure (16–23%) compared to women without HIV (9%) [ 12 ] (historic assumptions in Rao et al .…”
Section: Methodsmentioning
confidence: 99%
“…Persons with CIN2+ were referred for colposcopic evaluation with biopsy, and women with confirmed lesions or cancer were treated with large loop excision of the transformation zone (LLETZ) or hysterectomy, respectively [ 18 ]. High loss-to-follow-up resulted in low levels of effective treatment with this three-visit strategy [ 19 ]. Effective treatment was lower for women living with HIV, reflecting lower sensitivity and specificity with cytology [ 9 , 10 ] and higher treatment failure (16–23%) compared to women without HIV (9%) [ 12 ] (historic assumptions in Rao et al .…”
Section: Methodsmentioning
confidence: 99%
“… 9 , 10 South Africa has set itself the same target of 70% screening coverage; however, this target was not met for the period 2000–2004, nor for the period 2005–2014 according to the National Health Laboratory Service (NHLS) national cytology statistics. 11 , 12 Furthermore, it has been shown that coverage of cervical cancer screening in South Africa may be as low as 19.3%. 2…”
Section: Introductionmentioning
confidence: 99%
“…The South African national guidelines recommend three-yearly screening from the time of HIV diagnosis. 11 , 12 , 13 …”
Section: Introductionmentioning
confidence: 99%
“…8 Poor access to screening, long waiting times for treatment of pre-cancerous cervical lesions as well as the socioeconomic inequities that exist in the country contribute to the high burden of ICC in South Africa. 9,10 Spatiotemporal analysis of ICC incidence among HIV positive women can be used for disease surveillance over time and space, and to identify potential causes of the unequal distribution of ICC incidence. In this nationwide study in South Africa during 2004-2014, we examine the spatiotemporal incidence of ICC among women diagnosed with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…8 Poor access to screening, long waiting times for treatment of pre-cancerous cervical lesions as well as the socioeconomic inequities that exist in the country contribute to the high burden of ICC in South Africa. 9,10…”
Section: Introductionmentioning
confidence: 99%